2008
DOI: 10.1080/03079450802356946
|View full text |Cite
|
Sign up to set email alerts
|

Avian hepatitis E virus infection and possible associated clinical disease in broiler breeder flocks in Hungary

Abstract: In broiler breeder flocks in one broiler integration in Hungary, a new syndrome appeared in January 2005 with initially four successive post-peak flocks experiencing significant decreases in egg production. Clinically birds became depressed and there was a small increase in the mortality rate. Postmortem examinations revealed enlarged livers in up to 19% of birds dying, and enlarged spleens in some. Also observed were birds with either clotted blood or serosanguineous fluid in the abdomen and subcapsular haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 19 publications
2
42
0
4
Order By: Relevance
“…In Australia and Europe, clinically similar disease pictures and the presence of hepevirus have been reported (Handlinger & Williams, 1988;Massi et al, 2005;Morrow et al, 2008;Todd et al, 1993). However, at the molecular level, only a short sequence of the helicase domain in the ORF1 region created a link between possible aetiological agents of these two diseases (Haqshenas et al, 2001;Payne et al, 1999).…”
Section: Phylogenetic Analysis Of Avian Hev Strains Implies the Existmentioning
confidence: 86%
See 1 more Smart Citation
“…In Australia and Europe, clinically similar disease pictures and the presence of hepevirus have been reported (Handlinger & Williams, 1988;Massi et al, 2005;Morrow et al, 2008;Todd et al, 1993). However, at the molecular level, only a short sequence of the helicase domain in the ORF1 region created a link between possible aetiological agents of these two diseases (Haqshenas et al, 2001;Payne et al, 1999).…”
Section: Phylogenetic Analysis Of Avian Hev Strains Implies the Existmentioning
confidence: 86%
“…The virus material for sequencing isolate EaHEV (05-5492) was obtained from the liver of a bird displaying hepatomegaly, splenomegaly and severe abdominal bleeding (Morrow et al, 2008). The material for sequencing isolate AaHEV (06-561) was obtained from an FTA Classic Card with liver smears of birds experiencing symptoms of classical BLS, provided by P. Curtin (Goulburn, New South Wales, Australia) and A.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the RT-PCR methods for detection of avian HEV RNA are based on degenerate primer binding within ORF1 (15) and on a nested approach applying degenerate primers binding within ORF1 and ORF2 (30). These primers were developed for isolates from North America but were also successfully used for RT-PCR detection of European and Australian avian HEV (2,21,22,25,28). Recent studies revealed that ORF3 is the most conserved region of avian HEV (2).…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of antibodies was also detected in healthy chicken flocks and avian HEV was isolated from apparently healthy chicken flocks (30). In Europe, a wide distribution of avian HEV has been reported (2,21,22,25,28,32).…”
mentioning
confidence: 93%
“…Later on, these two viral agents proved to be variants of the same virus (known as aHEV). aHEV has now been detected in countries such as Spain (Peralta et al, 2009), Hungary (Morrow et al, 2008) and Canada (Agunos et al, 2006). aHEV was previously recognized as a member of the genus Hepevirus within the family Hepeviridae, which also includes swine and human HEVs .…”
Section: Introductionmentioning
confidence: 99%